Effects of an immersive virtual reality‐based classroom on students’ learning performance in science lessons - Liu, Ruixue; Wang, Lei; Lei, Jing; Wang, Qiu; Ren, Youqun (British journal of educational technology, 2020)
The increased availability and development of immersive technologies have given students growing opportunities to engage in different educational subjects. However, there is a lack of empirical research exploring the educational influence of using Immersive Virtual Reality (IVR) in science classrooms. To address this gap, this study developed a series of IVR‐based science lessons for middle‐school students and further examined these lessons’ effects on learning performance. Our quasi‐experimental approach employed a pretest and posttest to measure academic achievement and questionnaires to measure engagement and technology acceptance. A total of 90 sixth‐grade students from two classes were randomly assigned to the experimental and control groups. The experimental group engaged with the science lessons using Head‐Mounted Displays, whereas the control group learned the same material through traditional teaching methods. The results revealed that the experimental group obtained significantly higher academic achievement and engagement scores (cognitive, behavioral, emotional and social) than the control group. Moreover, the experimental group had a high level of technology acceptance for IVR usage in classrooms. Our study provides empirical evidence for IVR’s use in science education. Furthermore, it also sheds light on how to develop and implement an IVR‐based classroom for formal educational purposes.